Metabolic dysregulation in MASLD-associated HCC: diagnostic biomarkers and therapeutic opportunities - Geng, Yu; Liu, Lanqing; Sun, Yongping; Guo, Lijuan; Wu, Yuanjing; Jia, Zhen (Frontiers in Medicine, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD), previously referred to as non-alcoholic fatty liver disease (NAFLD), has become the most common chronic liver disease globally, with its incidence rising annually. MASLD is closely linked to metabolic syndrome and can progress from simple steatosis to more severe stages, including non-alcoholic steatohepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma (HCC), affecting 13%–38.2% of cases. Notably, in 40%–50% of patients, this progression occurs without cirrhosis. The dysregulation of glucose and lipid metabolism is a fundamental pathological mechanism in MASLD and its transition to HCC. Key factors include insulin resistance, increased gluconeogenesis, impaired β-oxidation, oxidative stress, and chronic inflammation, all of which contribute to a tumor-promoting hepatic microenvironment. This review provides a comprehensive analysis of the latest research on MASLD-related HCC, emphasizing disturbances in glucose metabolism (such as disrupted hepatic insulin signaling, key enzymes like G6Pase and PK, and miRNAs such as miR-22-3p that induce Warburg effects), lipid imbalances (for example, upregulation of FASN/ACC and downregulation of PPARα targets like CPT1A), and the crosstalk between various pathways (including mTORC1, AMPK/ACC, FXR, and NF-κB/JNK). It also explores metabolic regulators such as DKK3, FGF21, and O-GlcNAcylation, and examines the role of the gut microbiota in modulating short-chain fatty acids, bile acids, and NLRP3 inflammasome activation in disease progression. By integrating the latest advancements in basic and clinical research, this article presents a solid theoretical framework for early diagnosis, risk assessment, biomarker development, and precision therapies. It also highlights promising therapeutic targets, including PPARα agonists, mTOR inhibitors, FGF21 analogs, and microbiota interventions, while proposing future directions in multi-omics and personalized treatment strategies.